Surface-modified graphene oxide as an additive in aluminium-based metal fuel - Gong, Wenbin (Nanyang Technological University, 2024)
This study explores the integration of graphene oxide (GO) and its surface functionalized derivative (FGO) with aluminium (Al) micro- and nano-particles metal fuels to alter their combustion properties. Aluminium, known for its abundant presence and high energy density, poses high potential in the study of metal fuel applications. By incorporating GO and FGO into aluminium, we aim to leverage graphene's high surface area and fluorine's reactive nature to improve combustion kinetics. We synthesized GO and FGO in the lab and prepared GO/Al and FGO/Al composites with varying additive contents for micron- and nano-sized Aluminium. These composites were analysed through thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), bomb calorimetry, and dynamic pressure measurement to evaluate their thermal and combustion properties. Our findings suggest that the surface modification of graphene oxide with Fluorolink E10-H, a fluorine-containing oligomer, positively influences the reaction kinetics, notably in the aspects of energy release and combustion characteristics thereby offering a promising approach to optimizing aluminium-based metal fuels for energetic applications.